2016
DOI: 10.1109/jcn.2016.000061
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging proxy mobile IPv6 with SDN

Abstract: Abstract:The existing Proxy Mobile IPv6 suffers from a long handover latency which in turn causes significant packet loss that is unacceptable for seamless realtime services such as multimedia streaming. This paper proposes an OpenFlow-enabled proxy mobile IPv6 (OF-PMIPv6) in which the control of access gateways is centralized at an OpenFlow controller of a foreign network. The proposed OF-PMIPv6 separates the control path from the data path by performing the mobility control at the controller, whereas the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…PMIPv6 is a network-based mobility management protocol where a core entity called the local mobility anchor (LMA) plays the role of the physical mobility anchor point to establish the appropriate tunnel with mobility access gateways (MAGs) after handover based on the binding updates of the user information. Compared to the legacy PMIPv6-based architecture, where LMA and MAG nodes are physically deployed in the forwarding plane, the SDN-based PMIPv6 separates the mobility functions of LMA and MAG from the forwarding plane nodes, which can provide efficient route management in the forwarding plane [17,18].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…PMIPv6 is a network-based mobility management protocol where a core entity called the local mobility anchor (LMA) plays the role of the physical mobility anchor point to establish the appropriate tunnel with mobility access gateways (MAGs) after handover based on the binding updates of the user information. Compared to the legacy PMIPv6-based architecture, where LMA and MAG nodes are physically deployed in the forwarding plane, the SDN-based PMIPv6 separates the mobility functions of LMA and MAG from the forwarding plane nodes, which can provide efficient route management in the forwarding plane [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we analyze the performance of the proposed scheme in terms of the handover signaling cost, UL/DL handover delay, and packet loss compared to the SDN-based PMIPv6 [16,17] and SDN-based EPC [23,24,49]. Among the conventional schemes, the basic handover procedure for SDN-based PMIPv6 is same as that of Class 1 in Figure 2a, such as the SDN mobility signaling flow [17] and reactive OpenFlow-PMIPv6 handover signaling flow [18]. In the case of the SDN-based EPC, we assume that the architecture is the full-SDN EPC architecture [24], where all of the control plane entities such as MME and HSS are implemented in the SDN controller for a fair comparison with the SDN-based PMIPv6.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Most of the proposed SDN architectures in wireless networks cannot be directly applied to large-scale networks due to this reason [35]. OpenFlowenabled proxy mobile IPv6 (OF-PMIPv6) is proposed in [36] where the control path is separated from the data path by performing the mobility control at the controller, whereas the data path remains direct between the MAG and the LMA in an IP tunnel form. This method achieves improved handover latency over conventional Proxy MIPv6, while the data plane anchor problem is persistent.…”
Section: Related Workmentioning
confidence: 99%
“…In the proactive OF-PMIP Open Flow based Proxy Mobile IP the IP tunnel status of MN is maintained by the Open Flow Mobile Access Gateway (OMAG) as temporary or conclusive. In[9] it is further established that proactive OF-PMIP indicates lower latency as compared to the PMIP or reactive OF-PMIP and supports seamless mobility and no disruption on real time services giving QoS experience to the mobile users.…”
mentioning
confidence: 99%
“…it was observed that Mobile IP suffers from long handover latencies causing packet loss as mobile moves from one domain to the other, there are tunneling overheads, signaling overhead due to multiple registrations, consumes large amount of network performance and the extra binding update creates and overhead. To enable no changes in MN during handover in[9] explores the Proxy Mobile IP (PMIP) ISSN: 2414-4592 DOI: 10.20474/jater-5.2.3…”
mentioning
confidence: 99%